Not half no end : militantly melancholic essays in memory of Jacques Derrida - Bennington, Geoffrey (Frontiers of theory., 2010)
This book gathers essays written by Geoffrey Bennington since the death of his friend Jacques Derrida in 2004. All, with significant variations of depth, manner and tone dictated by the different circumstances for which they were written, continue the ongoing work of elucidating difficult and complex thought, often enough with reference to Derrida's persistent interrogation of the concepts of life and death, mourning and melancholia, and what he sometimes calls 'half-mourning'. This is a kind of mourning not so much 'failed' as suspended in the name of mourning itself, an 'ethical' interruption of the drive to complete mourning (the drive to get over it and get back to oneself and back to work), an interruption that Not Half, No End relates to the persistent but still ill-understood motif of interrupted teleology, which, it is argued here, is definitive of deconstruction in general. This suspension or interruption of the end (which is none other than differance 'itself' holding difference short of opposition and its dialectical totalisation, so that differance is always not half difference, less than absolute) has all manner of consequences for our thinking, and for how we attempt to categorize that thinking (as epistemological, ethical, political or aesthetic, for example). Not Half, No End moves through all these domains, and the whole of Derrida's rich and varied corpus, in a weave or scatter of styles, from the expository and analytic to the autobiographical and the confessional, in the ongoing process of deconstruction. Key Features New collection of essays by major theorist Expanded readings of late texts by Derrida Research monograph on mourning and melancholy First consideration of the legacy of Derrida by a co-author